DETERMINING LEAN PRINCIPLE FACTORS TO ACHIEVE SUSTAINABLE CONSTRUCTION WITH TIME REDUCTION EMPHASIS - Muhamad Azani Yahya (Tesis, 2020)
The aim of this research is to determine the Lean Principles factors to achieve sustainable construction with time reduction emphasis. The methodology of mix methods consists of literature review, interviews, questionnaire, survey and shceduling simulation.